2020
DOI: 10.1021/acsami.0c12899
|View full text |Cite
|
Sign up to set email alerts
|

Green and Efficient Inkjet Printing of Cotton Fabrics Using Reactive Dye@Copolymer Nanospheres

Abstract: Digital inkjet printing of textiles possesses great advantages like high efficiency and flexible production, but the challenges like the risk of causing serious environmental problems due to the large usage of dyes and chemicals still remain a matter of concern. In response to this problem, herein, a novel kind of reactive dye@copolymer nanosphere was prepared through the adsorption of C. I. Reactive Red 218 dyes (RR218) onto cationic poly(styrene-butyl acrylate-vinylbenzyl trimethylammonium chloride) (PSBV) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…17,18 The dye is modified to improve the resolution and adjust ink formula. 19,20 Surfactants such as naphthalene sulfonic acid are added into the ink to adjust the surface tension and other important parameters for stable droplet behavior. 8 In order to obtain stable droplets, it is necessary to adjust the parameters to avoid air pollution by tiny droplets.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 The dye is modified to improve the resolution and adjust ink formula. 19,20 Surfactants such as naphthalene sulfonic acid are added into the ink to adjust the surface tension and other important parameters for stable droplet behavior. 8 In order to obtain stable droplets, it is necessary to adjust the parameters to avoid air pollution by tiny droplets.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Some researchers have conducted various studies to improve the resolution of ink-jet printing images, which is closely related to the ink droplet shape. , Different types and amounts of organic solvents are added into reactive dye inks to obtain more stable droplets and high-quality images, which is conducive to improve dye efficiency. , The dye is modified to improve the resolution and adjust ink formula. , Surfactants such as naphthalene sulfonic acid are added into the ink to adjust the surface tension and other important parameters for stable droplet behavior . In order to obtain stable droplets, it is necessary to adjust the parameters to avoid air pollution by tiny droplets …”
Section: Introductionmentioning
confidence: 99%
“…Various studies have researched and developed materials for inkjet printing for printing on fabrics. Song et al [172] synthesized RR218@PSBV by the absorption of RR218 (red dye 218) onto PSBV (poly (styrene-butyl acrylatevinylbenzyl trimethylammonium chloride) nanospheres and inkjet-printed it on cotton fabric, as shown in Fig. 14-a.…”
Section: A Digital Textile Printingmentioning
confidence: 99%
“…14-a. The dye@copolymer nanosphere improved the color performance, image quality, and material conservation [172]. In [173], two reactive red dyes, RR218 and reactive red 24:1 were inkjet-printed and the resulting droplets were compared.…”
Section: A Digital Textile Printingmentioning
confidence: 99%
“…Digital inkjet printing as a new environmental technology has been initially applied in the textile industry. It has unique superiorities such as low cost, high precision, and celerity compared with traditional printing which was limited to produce high-quality and personalized products. Among all kinds of dye-based inks, reactive dye ink accounts for an increasing proportion. It has the advantages of bright color, comprehensive color range, good level dyeing, and high fastness, and it can form covalent bonds with both cotton and wool fabrics. Plenty of research studies reported that reactive dye inkjet printing has been successfully used for cotton fabrics as it shows cotton’s characteristics of reproducibility, good dyeability, and low cost. , However, there are few articles reporting about its application in wool fabrics.…”
Section: Introductionmentioning
confidence: 99%